Analyzing Transportation Logistics and Infrastructure Sustainability in the Iberian Peninsula: The Case of Portugal Mainland. Issue 12 (2nd December 2022) - Naranjo Gómez, José Manuel; Castanho, Rui Alexandre; Vulevic, Ana
ABSTRACT: Transportation is one of the most meaningful references of unsustainability in regional urban areas. This difficulty is stimulating urban planners and decision-makers to introduce the concept of sustainability into their policy design at multiple levels. Contextually, through exploratory tools, the present study aims to analyze the impacts over the socio-economic sphere that those new plans could bring to the region and the local populations of Portugal Mainland. Also, analyses of regional disparities in Portugal focused on the socio-economic aspects and analyses on territorial cohesion concept where indicators organized in policy-oriented territorial objectives and then combined with an analytical framework. Besides, the study especially intends to cover sustainable accessibility (also one of the components of territorial cohesion), which aims to help regional planners determine the inherent obstacles and design possible alternatives at the strategic planning level for sustainable regional transport and land-use arrangement. The study shows that exist inequalities in the distribution of absolute accessibility. Value of accessibility in category "very high" in 192 towns (68, 57%) settlements, in the central, coastal territory along the dual carriageway and national road corridors, live 81, 7% population. Nevertheless, the regional inequalities pattern did not vary considerably in Portugal's last decade of funding policies.